2020
DOI: 10.1021/acs.energyfuels.0c02591
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Charged Nanogels for Interfacial Tension Reduction and Emulsion Stabilization at Various Salinities and Oil Types

Abstract: Nanoparticles have been widely investigated for their mechanisms in enhanced oil recovery, such as rock wettability alternation, oil displacement by disjoining pressure, and the stabilization of emulsion and foam. Nanogels are nanosized cross-linked polymeric particles that have the properties of both nanoparticles and hydrogels. The goal of this study is to investigate the oil–water interfacial behavior in the presence of nanogels, especially the dynamic interfacial tension and the stability of oil-in-water (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…It was indicated that nonspheric emulsifiers had a better package efficiency and heterogeneous resistance than JPs, which was ascribed to their higher degree of rotational bending and larger adsorption areas of JFs on the droplet surface . In addition, the water–oil interfacial tension in the presence JFs was 12 mN/m, which was lower than that of JPs-stabilized emulsions (15 mN/m), indicating an easier formation of emulsions by JF emulsifiers . Compared with a point-to-point conformation of JPs, JFs showed a side-to-side conformation between oil and water phases, which caused a better heterogeneous resistance .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was indicated that nonspheric emulsifiers had a better package efficiency and heterogeneous resistance than JPs, which was ascribed to their higher degree of rotational bending and larger adsorption areas of JFs on the droplet surface . In addition, the water–oil interfacial tension in the presence JFs was 12 mN/m, which was lower than that of JPs-stabilized emulsions (15 mN/m), indicating an easier formation of emulsions by JF emulsifiers . Compared with a point-to-point conformation of JPs, JFs showed a side-to-side conformation between oil and water phases, which caused a better heterogeneous resistance .…”
Section: Resultsmentioning
confidence: 99%
“…46 In addition, the water−oil interfacial tension in the presence JFs was 12 mN/m, which was lower than that of JPs-stabilized emulsions (15 mN/m), indicating an easier formation of emulsions by JF emulsifiers. 47 Compared with a point-to-point conformation of JPs, JFs showed a side-to-side conformation between oil and water phases, which caused a better heterogeneous resistance. 48 In addition, due to the formation of side-to-side conformation, JFs could slide better along the major axis while the vertical and rotational translations were limited.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The composite emulsions reached their lowest interfacial tension value at a NaCl concentration of 0.08 mol/L, which may be attributed to the disordered structure of the protein at the oil-water interface led to a rapid change in its conformation with increasing NaCl concentration, which reduced the interfacial tension and produced a lower equilibrium interfacial tension over time [38]. Secondly, due to the hydrophilicity of OVA, the addition of salt ions significantly reduced the dispersion of the emulsion extremely low, which led to the gradual stabilization of the composite solution and resulted in lower energy of the entire system [39]. Furthermore, the inclusion of NaCl, comprising sodium and chloride ions, reduced the electrostatic repulsion between charged emulsions at the oil-water interface.…”
Section: Interfacial Tension Of Ova-xg Complex Solutionsmentioning
confidence: 99%
“…Based on the results of plugging and displacement experiments, the oil displacement mechanism of polymer microspheres can be analyzed. Parameters such as interfacial tension, structural separation pressure, wettability, emulsification, and sweep efficiency are also subjected to relevant testing and analysis [29,30].…”
Section: Characterization Of Polymer Microspheresmentioning
confidence: 99%